Evaluasi Hasil Belajar Tematik dan Implikasinya Terhadap Motivasi Belajar Siswa Sekolah Dasar - Srirahmawati, Ija; Putra, Angga; Hairunisah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The purpose of this research is to determine the evaluation of thematic learning outcomes and their implications for students' learning motivation. This research is a type of descriptive qualitative research which aims to explore the process of evaluating thematic learning outcomes. Research data collection techniques were carried out through several techniques, namely interviews, questionnaires, and documentation. The data analysis technique used is descriptive analysis. The research results show that the evaluation of learning outcomes varies for each student. This is due to differences in levels of learning ability and motivation. Assessment of learning outcomes is based on three aspects, namely cognitive, affective and psychomotor aspects. The evaluation results have an impact on learning motivation. Nine students who scored above the KKM had high and very high learning motivation with a percentage of 53%. Meanwhile, 6 students who obtained learning outcomes below the KKM had medium category learning motivation with a percentage of 47%. Thus it can be concluded that evaluation of learning outcomes also has an impact on student motivation. Therefore, as a teacher it is important to be able to improve learning activities so that students can achieve maximum competency.